Functionalization of hydrophobic surfaces with antimicrobial peptides immobilized on a bio-interfactant layer - Corrales-Ureña, Yendry Regina [UNESP]; Souza-Schiaber, Ziani; Lisboa-Filho, Paulo Noronha [UNESP]; Marquenet, Florian; Michael Noeske, Paul-Ludwig; Gätjen, Linda; Rischka, Klaus (Royal Society of Chemistry (RSC), 2019)
The design of functionalized polymer surfaces using bioactive compounds has grown rapidly over the past decade within many industries including biomedical, textile, microelectronics, bioprocessing and food packaging sectors. Polymer surfaces such as polystyrene (PS) must be treated using surface activation processes prior to the attachment of bioactive compounds. In this study, a new peptide immobilization strategy onto hydrocarbonaceus polymer surfaces is presented. A bio-interfactant layer made up of a tailored combination of laccase from trametes versicolor enzyme and maltodextrin is applied to immobilize peptides. Using this strategy, immobilization of the bio-inspired peptide KLWWMIRRWG-bromophenylalanine-3,4-dihydroxyphenylalanine-G and KLWWMIRRWG-bromophenylalanine-G on polystyrene (PS) was achieved. The interacting laccase layers allows to immobilize antimicrobial peptides avoiding the chemical modification of the peptide with a spacer and providing some freedom that facilitates different orientations. These are not strongly dominated by the substrate as it is the case on hydrophobic surfaces; maintaining the antimicrobial activity. Films exhibited depletion efficiency with respect to the growth of Escherichia coli bacteria and did not show cytotoxicity for fibroblast L929. This environmentally friendly antimicrobial surface treatment is both simple and fast, and employs aqueous solutions. Furthermore, the method can be extended to three-dimensional scaffolds as well as rough and patterned substrates.